From daily movements to population distributions: weather affects competitive ability in a guild of soaring birds - Shepard, Emily L. C. (2013)
The ability of many animals to access and exploit food is dependent on the ability to move. In the case of scavenging birds, which use soaring flight to locate and exploit ephemeral resources, the cost and speed of movement vary with meteorological factors. These factors are likely to modify the nature of interspecific interactions, as well as individual movement capacity, although the former are less well understood. We used aeronautical models to examine how soaring performance varies with weather within a guild of scavenging birds and the consequences this has for access to a common resource. Birds could be divided broadly into those with low wing loading that are more competitive in conditions with weak updraughts and low winds (black vultures and caracaras), and those with high wing loading that are well adapted for soaring in strong updraughts and moderate to high winds (Andean condors). Spatial trends in meteorological factors seem to confine scavengers with high wing loading to the mountains where theyout-compete other birds; a trend that is borne out in worldwide distributions of the largest species. However, model predictions and carcass observations suggest that the competitive ability of these and other birds varies with meteorological conditions in areas where distributions overlap. This challenges the view that scavenging guilds are structured by fixed patterns of dominance and suggests that competitive ability varies across spatial and temporal scales, which may ultimately be a mechanism promoting diversity among aerial scavengers.